Comparison of the effect of co-administration of crystalloid versus colloid, with phenylephrine infusion for the prevention of hypotension from spinal anesthesia during elective caesarian section - Frans, L. J. (University of Limpopo (Medunsa Campus), 2014)
Aim: To determine whether there is any difference when phenylephrine in-fusion is combined with either a crystalloid or a colloid in the prevention of symptomatic hypotension during spinal anaesthesia for caesarian section. Objectives: 1. To determine whether there is any difference in the total dose of phenylephrine needed to maintain normal blood pressure when crystalloid or a colloid is used. 2. To determine the number of women who develop symptoms (viz. dizziness, restlessness, nausea and vomiting) when phenylephrine infusion is combined with either a crystalloid or a colloid. 3. To determine the severity of symptoms in the phenylephrine plus crystalloid group versus the phenylephrine plus colloid group. 1 Sampling methods ,study designs and procedures Study design: A prospective, randomised, comparative study of women who had caesarian section under spinal anaesthesia was conducted. The aim was to determine whether giving a phenylephrine infusion plus a crys-talloid versus a phenylephrine infusion plus a colloid made a difference in the prevention of symptomatic hypotension. Sample criteria: Pregnant women undergoing caesarian section under spinal anaesthesia were selected and divided randomly into two groups; one to receive a phenylephrine infusion plus a crystalloid (group A), the other to receive a phenylephrine infusion plus a colloid (group B). Patients were excluded for the following reasons: 1. Absolute contra indications to spinal anaesthesia. 2. Emergency Caesarian section 3. Diabetes mellitus 4. Renal disease 2 Sample size: The necessary sample was determined to be 122 patients, each group having 61 patients. Procedures: Each patient received bupivacaine with dextrose (12.5 mg) plus sufentanyl 2.5μg intrathecally at L3-L4 intervertebral space. Patients in group A received 350ml of Ringer's Lactate over 15 minutes, started immediately after administration of anaesthesia, and 3ml of the same fluid for each 1ml of blood lost. Patients in group B received 150ml of Voluven (Hydroxyethyl starch 130/40) over 15 minutes, started immediately after administration of anaesthesia, and 1ml of the same fluid for each 1ml of blood lost. Each patient also received an infusion of phenylephrine (50μg/min), started within a minute of giving anaesthesia and stopped if the mean blood pressure exceeded the baseline by 20%. A 50ug bolus was given any time the mean blood pressure was 20% below the original. Non-invasive blood pressure measurements were taken every 2.5 minutes for 45 minutes. 3 At the end of the procedure patients were questioned for the following symptoms: dizziness, nausea, vomiting and restlessness (as observed by researcher).They were then classified as follows: asymptomatic, mildly symptomatic (symptoms discovered only on questioning), moderately symptomatic (patient complained about symptoms but not restless), or se-verely symptomatic (patient complained about symptoms and was rest-less). Statistical analysis The analysis was based on descriptive statistics with variables expressed as Mean± Standard deviation. Differences between the two groups were determined using the student t-test and conversion of the value of (t) to p-value. Differences were considered significant when the p-value was ≤ 0.05. Relational statistics were calculated using the Chi-Square analysis to reflect the association of the use of a crystalloid or colloid plus phe-nylephrine infusion, with prevention of hypotension during spinal anaesthe-sia for elective Caesarian section. 4 Results Blood pressure readings at the beginning and the end of measurement period were statistically similar between the two groups, suggesting equal effectiveness in maintaining blood pressure. The medians for the infused amounts and total amounts of phenylephrine were the same for both groups (2200μg).There was no statistically significant difference in the number of patients requiring rescue boluses of phenylephrine (p=0.52),nor was there a significant difference in the total amount of drug used as bo-lus(p=0.7).The majority of patients in both groups were asymptomatic(57% in group B and 69% in group A),with a p-value of 0.2. Most of these pa-tients experienced mild symptoms (63% in group A versus 64% in group B, p=0.8). Conclusion The results of this study suggest there is no added advantage in using a colloid co-administration with a phenylephrine infusion to prevent hypoten-sion during spinal anaesthesia for elective caesarian section. A crystalloid co-administration is equally effective.
Thesis (M Med (Anaesthesiology)) -- University of Limpopo, 2012.
Keywords: Phenylephine.; Colloids.